2013
DOI: 10.1083/jcb.201211039
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated waves of actomyosin flow and apical cell constriction immediately after wounding

Abstract: Epithelial wounding causes waves of actomyosin flow and apical cell constriction that are dependent on calcium signaling and actin filament severing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
226
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(253 citation statements)
references
References 50 publications
16
226
3
Order By: Relevance
“…Wound closure during axis elongation is driven by the apical constriction of the wounded cells in combination with the assembly of an actomyosin purse string by the cells adjacent to the wound (Fernandez-Gonzalez and Zallen, 2013). At later stages of development, deformation of cells around the wound drives calcium influx through mechanically gated channels and promotes the assembly of the actomyosin purse string (Antunes et al, 2013). However, little is known about the cell morphology changes that accompany wound repair during axis elongation.…”
Section: Automated Quantification Of Wound-closure Dynamics: Validatimentioning
confidence: 99%
“…Wound closure during axis elongation is driven by the apical constriction of the wounded cells in combination with the assembly of an actomyosin purse string by the cells adjacent to the wound (Fernandez-Gonzalez and Zallen, 2013). At later stages of development, deformation of cells around the wound drives calcium influx through mechanically gated channels and promotes the assembly of the actomyosin purse string (Antunes et al, 2013). However, little is known about the cell morphology changes that accompany wound repair during axis elongation.…”
Section: Automated Quantification Of Wound-closure Dynamics: Validatimentioning
confidence: 99%
“…The mechanical induction of myosin assembly could occur through regulation of the G protein-coupled receptor pathway that activates RhoA, with mechanical stimulation increasing plasma membrane tension and decreasing endocytic downregulation of the receptor, thus elevating pathway activity (Pouille et al, 2009). Recent studies of wound healing demonstrated that apical constriction in response to wounding is associated with cytoplasmic calcium accumulation through a stretch-activated calcium channel (Antunes et al, 2013). During Drosophila dorsal closure, calcium signaling has been shown to promote contractility, and two ion channels were identified as being required for embryos to regulate force generation after laser ablation (Hunter et al, 2014).…”
Section: Possible Roles For Mechanical Feedback and External Constraintsmentioning
confidence: 99%
“…Apical constriction of individual cells can contribute to cell ingression from epithelial tissues, sometimes as a step in an epithelialmesenchymal transition (EMT) (Anstrom, 1992;Nance and Priess, 2002;Harrell and Goldstein, 2011;Williams et al, 2012). Apical constriction is also associated with the extrusion of apoptotic or delaminating cells (Toyama et al, 2008;Slattum et al, 2009;Marinari et al, 2012) and wound contraction and healing (Davidson et al, 2002;Antunes et al, 2013). Thus, apical constriction remodels epithelia in a variety of ways to achieve proper tissue shape and structure.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, mechanobiology is an expanding interdisciplinary field between biology and physics (Iskratsch et al 2014). Changes in the mechanical property of a cellular sheet may be caused by physical damage and subsequent wound-healing processes (Antunes et al 2013) and by cell death (Teng and Toyama 2011;Toyama et al 2008) in addition to cellular size and shape changes. …”
Section: Physical Distortion Hypothesismentioning
confidence: 99%